EDUCATIONAL ISSUES IN BUKHARA DURING THE YEARS OF SOVIET POWER (TAMADDUN NURI JURNALI, 2024)
This article covers the issues of education in Bukhara during the years of Soviet power (1925-1941). The fact that Faizulla Khojaev has done a lot of work for the development of the school has been analyzed through statistical data in his works. The issues of school buildings, supplies, lessons and textbooks, teachers' salaries, and the condition of teachers and students during this period are described.